AIAA Guidance, Navigation, and Control Conference and Exhibit 2002
DOI: 10.2514/6.2002-4586
|View full text |Cite
|
Sign up to set email alerts
|

Task Allocation for Wide Area Search Munitions via Iterative Network Flow

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, DISTRIBUTION/AVAILABILITY STATEMENTApprov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 4 publications
0
53
0
Order By: Relevance
“…Finally, one needs to search the cost table for the directed graph to find a state transition sequence of minimum cost that starts with the initial state and covers all the targets. Several publications 1,2,9 in the literature have addressed the search problem and that is not the topic under investigation in this paper. As our interest is in demonstrating the effect of wind on the task assignment problem, we consider two examples with 3 targets each and the direct graph search was done manually with some effort.…”
Section: Optimal Tour Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, one needs to search the cost table for the directed graph to find a state transition sequence of minimum cost that starts with the initial state and covers all the targets. Several publications 1,2,9 in the literature have addressed the search problem and that is not the topic under investigation in this paper. As our interest is in demonstrating the effect of wind on the task assignment problem, we consider two examples with 3 targets each and the direct graph search was done manually with some effort.…”
Section: Optimal Tour Planningmentioning
confidence: 99%
“…[1][2][3] This new paradigm for control has been implemented in the MultiUAV simulation platform by the Air Force Research Laboratory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Dunkel and Gozaydin have improved the decision process to control the actions of the group rather than the individual. Furthermore, the decision methodology was based upon a mathematically rigorous approach, [9], which eliminated the need for pre-optimized decision rules tuned for specific scenarios. Using this formulation, Dunkel and Gozaydin demonstrated that while cooperative attack alone does not always improve mission effectiveness, cooperative classification used in conjunction with cooperative attack does improve overall group efficiency.…”
Section: Figure 1-1 Usaf Locaas Design Conceptmentioning
confidence: 99%
“…The following cooperative team process [11] is intended to contrast the differences to the non-cooperative case. [3], [9], [14], [16], [13] has explored the affects these three items can have on cooperative control. Item 3 is of special interest for successfully employing cooperative teams to perform tasks.…”
Section: -4mentioning
confidence: 99%